The Transformation of Indonesian Ulama Writing in Negotiations of Islamic Intellectual Authority - Fadli R, Syahrul; Yuliani, Yuliani; Yuliarni, Yuliarni; Salsabila, Mira; Maigus, Maigus; Amat, Ali; Sabri, Ahmad; Sukmareni, Sukmareni (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This research aims to analyze the doctrinal construction of the writing tradition in Islam, examine the historical dynamics of Indonesian scholars' writing traditions from the 19th to the 21st century, and identify structural and cultural factors influencing its development. This study uses a qualitative approach with a library research method. Data were collected from primary and secondary sources, including scholarly books, academic references, journal articles, and other relevant publications. Data analysis was conducted through content analysis, historical, and conceptual approaches to comprehensively understand the development of scholarly writing traditions. The results show that the Islamic writing tradition has a strong epistemological foundation through the concepts of iqra', al-qalam, and the codification of knowledge (tadwīn al-'ilm), which encourage literacy culture and knowledge production. Historically, the writing tradition of Indonesian scholars developed significantly in the 19th century through transnational Islamic intellectual networks, experienced challenges during the colonial period due to changes in education systems and power structures, and transformed in the modern era through print and digital media. Supporting factors for this tradition include networks of scholars, Islamic boarding schools, educational institutions, and access to knowledge sources. Meanwhile, inhibiting factors include colonial intervention, secularization of education, limited literacy culture, and changing patterns of information consumption in the digital era. This study confirms that the writing tradition of Indonesian scholars is dynamic and adaptive, requiring the strengthening of literacy ecosystems to sustain Islamic knowledge production in the future.